Divide and connect: divorce by mutual consent, keeping in touch by desideratum - Bayer, Emmanuelle M. (Comptes Rendus Biologies, 2022)
Cell division is fundamental for living organisms, sustaining their growth and development. During cell division a single mother cell will duplicate its genome and organelles, and give rise to two independent entities that will eventually split apart in a tightly regulated process called abscission or the final-cut. In multicellular organisms, newly born daughter cells split apart while they simultaneously need to maintain contact for intercellular communication. In this mini-review, I discuss this fascinating paradox of how cells across kingdoms combine the need to divide with the need to connect.